2004
DOI: 10.1007/978-3-540-24680-0_133
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Data Grid Replication Strategy Based on Internet Hierarchy

Abstract: Abstract. In data grid, large quantity of data files is produced and data replication is applied to reduce data access time. Efficiently utilizing grid resources becomes important research issue since available resources in grid are limited while large number of workloads and large size of data files are produced. Dynamic replication in data grid aims to reduce data access time and to utilize network and storage resources efficiently. This paper proposes a novel dynamic replication strategy, called BHR, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 8 publications
0
89
0
Order By: Relevance
“…Also a dynamic replica optimization strategy (HRS) is suggested where the nearby data has a higher priority to access than to generate new replicas. The simulation results showed that HCS successfully reduced data access time and the amount of intercluster-communications in comparison with LRU (Least Recently Used), LFU (Least Frequently Used), BHR (Bandwidth Hierarchy-based Replication) [10]. Since the file transmission time is the most important factor to influence the job execution time for data-intensive jobs in data grids, HCS with HRS can reduce the file transmission time effectively by virtue of valid scheduling and proper data replication.…”
Section: Related Workmentioning
confidence: 99%
“…Also a dynamic replica optimization strategy (HRS) is suggested where the nearby data has a higher priority to access than to generate new replicas. The simulation results showed that HCS successfully reduced data access time and the amount of intercluster-communications in comparison with LRU (Least Recently Used), LFU (Least Frequently Used), BHR (Bandwidth Hierarchy-based Replication) [10]. Since the file transmission time is the most important factor to influence the job execution time for data-intensive jobs in data grids, HCS with HRS can reduce the file transmission time effectively by virtue of valid scheduling and proper data replication.…”
Section: Related Workmentioning
confidence: 99%
“…Usually, dynamic replication is triggered when the popularity of a file exceeds a certain threshold [13]. The authors of [15,18] use dynamic replication to conserve bandwidth in a hierarchical environment. The work in [9] studies the replication dynamics in different topologies such as ring, tree, and hybrid.…”
Section: Related Work On Replicationmentioning
confidence: 99%
“…To solve the problem of data loss in both cases (unpopularity or failure), we proposed, with some improvements, an approach of dynamic replication that combines replication that is based on the availability of the work proposed in [11,15] and replication based on the popularity of the work given in [8,16]. In this approach the minimum number of replicas for each piece of data is the number of replicas that meets the availability desired by the administrator.…”
Section: The Proposed Approachmentioning
confidence: 99%
“…Since every domain knows average number of access for each file and then deletes those files whose access is less than the average, and replicates other files in its local storage. In [4], an algorithm for a 2-level hierarchical structure based on internet hierarchy (BHR) has been introduced which only considers dynamic replication and does not consider scheduling. Nodes in the first level are connected to each other with high speed networks and in the second level via internet.…”
Section: Related Workmentioning
confidence: 99%
“…In large-scale data-intensive applications, data transfer time is the primary cause of job execution delay. To mitigate the effect of such problems and facilitate efficient system performance, replication strategies and algorithms are employed [4]. The replication mechanism determines which file should be replicated, when to create new replicas and where the new replicas should be placed.…”
Section: Introductionmentioning
confidence: 99%